(untitled) (Colombia Medica, 2008)
Introduction: The path of microsatellite instability has mainly been found in cancers of digestive tracts, of which 90% of cases are hereditary cancer patients and 15% are patients with sporadic cancer. That instability produces a phenotype called Microsatellite instability (IMI+) or phenotype by replication mistake (RER+) that leads to the accumulation of mutations in higher rates to normal. Objectives: To identify the presence of IMI+ phenotype in patients analyzed and evaluated its relationship with the differentiation histopathologic tumor, because which together have been associated with a better prognosis and improved response to treatment given to the patient. Methodology: DNA was extracted from blood samples (normal cells) and biopsy of the tumor (tumor cells) of the 23 patients who were included in the study and through the amplification by PCR and subsequent capillary electrophoresis was typified the microsatellite mononucleotidic BAT-26, who was employed by his sensitivity to detect IMI+ phenotype (95%). Finally, we made a statistical correlation between the microsatellite instability phenotype, the presence (IMI+) or the absence (IMI-), with histopathological findings using Fisher’s exact test. Results: In 17% of cases (4 patients) had IMI+: 3 of them with colorectal cancer (CRC) -2 cases possibly with hereditary cancer- and one with gastric cancer (GC). There was no association between phenotype IMI+ with the pathological diagnosis, age, sex and differentiation histopathologic tumor. Conclusion: We found the phenotype IMI + in 17% of cases without association with the degree of differentiation histopathologic tumor, possibly by the reduced number of samples analyzed, making it essential to review the methods of fixation, paraffin and storage tissue because current techniques hinder digestion of proteinase k and PCR.